Board Composition and Firm Performance: Evidence from Bangladesh - A. Rashid; A. De Zoysa; S. Lodh; K. Rudkin (Australasian Accounting, Business and Finance Journal, 2010)
This study examines the influence of corporate board composition in the form of representation of outside independent directors on firm economic performance in Bangladesh. Two hypotheses are developed to examine the relationship among composition of board memberships including independent directors and firm performance. An observation of 274 Bangladeshi firm-years is used in the study. A linear regression analysis is used to test the hypotheses. Results reveal that the outside (independent) directors cannot add potential value to the firm’s economic performance in Bangladesh. The idea of the introduction of independent directors may have benefits for greater transparency, but the non-consideration of the underlying institutional and cultural differences in an emerging economy such as Bangladesh may not result in economic value addition to the firm. The findings provide an insight to the regulators in their quest for harmonization of international corporate governance practices.
Keywords: Board of directors; Corporate governance; Firm performance; Meetings; Top management team